KESALAHAN SISWA PADA PEMECAHAN MASALAHPERTIDAKSAMAAN LINEAR SATU VARIABEL BERDASARKANPROSEDUR NEWMAN DITINJAU DARI PERBEDAAN GENDER - Ghalda Alifia Nazhira, - (2022)
This research was aimed to determine student errors in solving the problem of linear inequality one variable in terms of gender differences. The method used is qualitative method with apply phenomenological study design. Data collection techniques ini this research used test and interview to students. The test questions given are in the form of problem solving questions based on Newman indicators. The result of this research obtained errors made by male students and female students. Male students and female students make the same errors. Five errors made by male students and female students, (1) reading errors, (2) comprehension errors, (3) transformastion errors, (4) process skills errors, and (5) encoding errors. Keywords: Newman's Error, Problem Solving, Gender